2017
DOI: 10.4103/ijmr.ijmr_1319_14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile & complications of neurotoxic snake bite & comparison of two regimens of polyvalent anti-snake venom in its treatment

Abstract: Background & objectives:The optimal anti-snake venom (ASV) dose required to treat neurotoxic snake envenomation is not known. Low-dose ASV (national protocol: maximum dose 200 ml) may be as efficacious as the conventional regimen (100 ml six hourly till all symptoms disappear), but a direct comparison of the regimens is not available. The aim of this study was to test the efficacy of low-dose ASV regimen against the conventional high-dose regimen.Methods:The clinical profile of 51 patients with neurotoxic snak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A study from India reported no fatalities in 51 patients with neurotoxic snake envenomation after they were treated with a combination of antivenom therapy and mechanical ventilation. [28] In our study only a small number of patients (16.7%) with respiratory failure and who required mechanical ventilation received antivenom. The antivenom used during the study period is not among the products currently recommended by international specialists in this field.…”
Section: Discussionmentioning
confidence: 70%
“…A study from India reported no fatalities in 51 patients with neurotoxic snake envenomation after they were treated with a combination of antivenom therapy and mechanical ventilation. [28] In our study only a small number of patients (16.7%) with respiratory failure and who required mechanical ventilation received antivenom. The antivenom used during the study period is not among the products currently recommended by international specialists in this field.…”
Section: Discussionmentioning
confidence: 70%
“…The majority of primary outcome measures (82·1%) were unique to a single study. Amongst studies with shared primary outcome measures, three by Isbister et al adopted return of INR to less than two [ 23 , 24 , 31 ] and two studies measured duration of invasive ventilation [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…There have been just nine randomised controlled trials that have included participants with neurotoxicity, with a combined sample size of 492 [ 25 – 27 , 32 , 38 , 39 , 46 48 ]. All except one study [ 26 ] took place in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases of progressive painful swelling or bleeding, anti-venom administration and fasciotomy may be necessary 42 . Low dose anti-venom has been found to be as effective as high dose anti-venom for both neurotoxic and hematotoxic snake bites 43 . Early, empirical anti-venom is lifesaving, but good supportive care with mechanical ventilation is equally important and can lead to a good outcome 44 .…”
Section: Discussionmentioning
confidence: 99%